The relationship between alexithymia, empathy, willingness to fulfill the contract, and communication skills attitudes of rural-oriented tuition-waived medical students of China: a cross-sectional study - Zhang, Lining; Xu, Yuxuan; Gao, Leyan; Feng, Chen; Han, Guanqi; Zhang, Xuewen; Xu, Xintong; Tang, Aimin (Frontiers in Medicine, 2025)
BackgroundRural-oriented tuition-waived medical students (RTMSs) with good communication abilities can help avoid medical conflicts and ensure high-quality rural medical services. This study evaluated the influence of empathy, willingness to fulfill the contract, and alexithymia on RTMSs’ communication skills attitude, and explored the mediating roles of empathy.MethodsThis cross-sectional study, conducted between 3 and 27 April 2024, randomly selected three medical universities in Shandong Province responsible for training RTMSs, with 495 students enrolled as participants. The Jefferson Scale of Empathy-Student (JSPE-S), Communication Skills Attitude Scale (CSAS), Willingness to Fulfill the Contract Scale, and the 20-item TAS-20 were used for investigation. Statistical methods such as one-way ANOVA, exploratory factor analysis (EFA), bivariate correlation, and structural equation modeling (SEM) were used.ResultsAlexithymia had a significant direct negative impact on empathy (β = −0.26, p < 0.001). It also negatively affected communication skills attitude (β = −0.17, p < 0.001). Additionally, it reduced the willingness to fulfill the contract (β = −0.26, p < 0.001). Willingness to fulfill the contract had a significant direct positive impact on empathy (β = 0.26, p < 0.001) and communication skills attitude (β = 0.09, p < 0.001). In the mediation pathway between willingness to fulfill the contract and communication skills attitude, empathy had a significant mediating effect, 95% CI: 0.6602–1.7526. In the mediating pathway between alexithymia and communication skills attitude, empathy also had a significant mediating effect [95% CI: (−0.8955) − (−0.3292)].ConclusionSchools and policy makers can strengthen RTMSs’ professional ethics, career identity, and professional identity education, increase RTME policy publicity and public opinion guidance, strengthen RTME policy support and restraint measures, help RTME strengthen the willingness to fulfill the contract, overcome alexithymia, play the role of empathy as an intermediary, and then improve the communication skills attitude of RTMSs. This survey can provide a feasible new plan for promoting the construction of a good doctor–patient relationship and the high-quality development of rural medical service.